FENOMENA CYBER PIRACY BERBASIS INSTAGRAM DI MAN 2 PONOROGO - Ela Rohmawati; Asmah Rohma Fatul Fauziah; Cindy Marcella; Arzeti Ulul Hamidah; Nurul Malikah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2022)
This study aims to determine the phenomenon of cyberpiracy based on Instagram at MAN 2 Ponorogo. This study uses a qualitative approach; the type of research is descriptive analysis with data collection techniques in the form of interviews. The subjects in this study were 30 students at MAN 2 Ponorogo who were active users of Instagram. Most of them are users of the